2021
DOI: 10.3389/fpsyt.2021.498614
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Multidimensional Links Between Trait Mindfulness and Trait Empathy

Abstract: Empathy and mindfulness are currently major topics of scientific interest. Although it is well-known that mindfulness—typically as an outcome related to meditation—generates empathy at the state level, only a small number of studies have documented the trait (i.e., personality) level association between mindfulness and empathy. Furthermore, the underlying mechanisms (subcomponents and mediator variables) that support this association remain unclear. Thus, here, with a focus on the trait level, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…This supports the notion that mindfulness meditation practice encompasses and fosters trait mindfulness (Alhawatmeh et al, 2022;Himichi et al, 2021;Karl & Fischer, 2022;Kiken et al, 2015;Thiermann & Sheate, 2022), involving sustained attention to one's ongoing sensory, cognitive, and emotional experience, without giving in to the natural tendency to react, elaborate, or evaluate (Bishop et al, 2004;Keng et al, 2011;Papies et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…This supports the notion that mindfulness meditation practice encompasses and fosters trait mindfulness (Alhawatmeh et al, 2022;Himichi et al, 2021;Karl & Fischer, 2022;Kiken et al, 2015;Thiermann & Sheate, 2022), involving sustained attention to one's ongoing sensory, cognitive, and emotional experience, without giving in to the natural tendency to react, elaborate, or evaluate (Bishop et al, 2004;Keng et al, 2011;Papies et al, 2012).…”
Section: Discussionsupporting
confidence: 76%
“…The combination of mindfulness and physical activity may be impactful in increasing empathy levels in healthcare workers. Recent studies reported the impact of mindfulness on increasing empathy, compassion, and social behaviours towards helping others [8][9][10][11]. The findings of this study suggest the value of Tai Chi on enhancing empathy levels as evidenced by the increase in scores on the TEQ by all five participants.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, qualitative studies have found that empathy training enhances practitioners' professional identity and development, improves understanding and awareness of patient experiences, and improves practitioner-patient relationships [24]. In future research, Tai Chi could be considered as another approach for empathy training, since it contains both mindfulness and physical activity, which have separately shown to impact empathy levels in prior research [8][9][10][11][12]23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation